What We Find : Sullivan's Crossing #1 - Carr, Robyn (Don Mills, Ontario, Canada : Mira Books, 2016)
A Denver neurosurgeon relocates to the small rural town named after her ancestor in the aftermath of a wrongful malpractice suit to recover and reconnect with her estranged father.
Keywords: Neurosurgeons -- Malpractice -- Fiction; Fathers and daughters -- Fiction; Neurosurgeons -- Malpractice -- Fiction; Father-daughter relationship -- Fiction; Romance fiction